Cultural Values, U.S. Neighborhood Danger, and Mexican American Parents' Parenting - White, Rebecca M. B. (2013)
To begin accounting for cultural and contextual factors related to child rearing among Mexican American parents we examined whether parents' Mexican American cultural values and perceptions of neighborhood danger influenced patterns of parenting behavior in two-parent Mexican-origin families living in the U.S. To avoid forcing Mexican American parents into a predefined model of parenting styles, we used latent profile analysis to identify unique patterns of responsiveness and demandingness among mothers and fathers. Analyses were conducted using parent self-reports on parenting and replicated with youth reports on mothers' and fathers' parenting. Across reporters most mothers and fathers exhibited a pattern of responsiveness and demandingness consistent with authoritative parenting. A small portion of parents exhibited a pattern of less-involved parenting. None of the patterns were indicative of authoritarianism. There was a modicum of evidence for no nonsense parenting among fathers. Both neighborhood danger and parents' cultural values were associated with the likelihood of employing one style of parenting over another. The value of using person-centered analytical techniques to examine parenting among Mexican Americans is discussed.